Watching the watchers: Taskforce Argos and the evidentiary issues involved with infiltrating Dark Web child exploitation networks. (September 2019) - Bleakley, Paul
As the kind of technology used by offenders advances, it has become increasingly necessary for global law enforcement agencies to adopt proactive strategies in order to effectively combat the threat posed by the organisation of child exploitation networks on the Dark Web. In spite of concerns regarding the collection of evidence, Queensland Police's Taskforce Argos has cultivated a reputation for success in the covert infiltration of online forums dedicated to child exploitation material, due largely to the relatively loose restrictions placed on it, which allow officers to commit a wide range of criminal acts whilst conducting controlled undercover operations.